Effect of sintering parameters on phase evolution and strength of dental lithium silicate glass-ceramics - Lohbauer, Ulrich; Belli, Renan; Abdalla Alonso, Alexandre [UNESP]; Goetz-Neunhoeffer, Friedlinde; Hurle, Katrin (Elsevier, 2019)
Objective: With the establishment of CAD/CAM technology, competing lithium silicate based formulations have been introduced for clinical use, but little is known about their phase composition. Here we investigate a commercially available SiO2-Al2O3-K2O-Li2O-P2O5-ZrO2 system to evaluate the crystal phase evolution during the second heat treatment by changing the main crystallization parameters. Methods: With a focus on the final stage of crystallization, we characterized the dimensional changes in the crystallographic structure of the residual Li2SiO3 and the lithium orthophosphate (Li3PO4) phases with variations in crystallization parameters, i.e. time, temperature and cooling rate over the range of the glass transition temperature Tg. The phase fractions (crystalline and glass) and the sizes of coherent scattering domains (CSDs) were resolved by means of quantitative X-Ray Diffraction using Rietveld refinement combined with an external standard method (G-factor). Biaxial flexure testing was conducted to evaluate the influence of crystallization parameters on the characteristic strength and natural defect distribution. Results: An increase in crystallization temperature from 840 to 880 °C resulted in a significant reduction of the Li2Si2O5 content, which indicated a reversion of the Li2SiO3 to Li2Si2O5 phase transformation. Reduction to 800 °C had no significant effect. Furthermore, the CSD sizes of Li2SiO3 and Li3PO4 continuously increased with increasing temperature, which was accompanied by an increase in strength parameters. Reducing the cooling rate over the range of Tg resulted in an increased strength at low failure probabilities. Significance: These findings help to establish recommendations for adjustment of the crystallization protocol, which has potential to increase the clinical reliability of the material investigated.
Keywords: Ceramics; Crystallization; Materials science; Restorative materials; X-ray Crystallography